Unveiling the burden of COPD: perspectives on a patient-reported outcome measure to support communication in outpatient consultations—an interview study among patients - Gronhaug, Louise Muxoll; Farver-Vestergaard, Ingeborg; Frølund, Jannie Christina; Lindström Egholm, Cecilie; Ottesen, Anders Løkke (Frontiers in Rehabilitation Sciences, 2024)
IntroductionChronic Obstructive Pulmonary Disease (COPD) profoundly affects physical, psychological, and social aspects of life, yet these issues often remain unaddressed. Patient-Reported Outcomes Measures (PROM) have the potential to address these issues by promoting person-centered communication. However, their impact in COPD practice remains uncertain. This study aimed to investigate how patients with COPD perceive the usefulness of a new holistic PROM for general palliative care (PRO-Pall) before and during outpatient consultations.MethodsSemi-structured telephone interviews were conducted with patients diagnosed with moderate to very severe COPD, 2-5 days after consultation at a respiratory outpatient clinic in Denmark. Interviews were transcribed verbatim and analyzed inductively using qualitative content analysis.ResultsNine patients (five males; mean age: 66 years) participated in the study with four themes emerging: (1) Unlocking thoughts: Completing PRO-Pall stimulated patients’ self-reflection, which revealed previously overlooked COPD-related issues, particularly psychosocial challenges. (2) Unmasking concerns: Patients felt encouraged to be honest, rather than concealing their concerns. (3) Breaking the ice: PRO-Pall responses enabled direct questioning by healthcare professionals during consultations, initiating discussions on patients’ sensitive yet vital COPD-related matters. (4) Deepening the dialogue: Healthcare professionals’ targeted and attentive approach fostered more holistic and meaningful discussions, providing most patients with a deeper understanding of psychosocial issues affecting their well-being.ConclusionCompleting PRO-Pall prior to outpatient consultations prompted most patients with COPD to unveil previously unacknowledged psychosocial challenges. During consultations, addressing these challenges initiated open discussions on individual concerns, enhancing most patients’ understanding of the multifaceted burden of COPD.